Change Management and Organizational Culture at PT XYZ: Lewin, Kotter, and Schein's Cultural Model Approach - Aprianto, Nanang; Vincent, Louise; Restianda, Randy (Jurnal Indonesia Sosial Sains, 2026)
This study aims to analyze the implementation of change management and the dynamics of organizational culture at XYZ's in facing digital transformation. Work system changes were made to improve efficiency and data accuracy. The approach used was descriptive qualitative with a case study method. Data were obtained through informal interviews and observations with analysis using Lewin and Kotter's change theory and Schein's organizational culture. The results show that the implementation of XYZ's change management occurred starting from the unfreeze, change, and refreeze stages and fulfilled Kotter's 8 Steps stages with an organizational culture moving towards digital and collaborative, although resistance still arises from some senior employees. Factors supporting the change include management support, technological infrastructure, and training for employees. Meanwhile, factors inhibiting the change come from low digital literacy and employee unpreparedness. This indicates that an adaptive culture needs to be strengthened through leadership and continuous human resource development.